Two patients with rare mixed adenoneuroendocrine carcinomas of the rectum. (12th March 2018) - Gül-Klein, Safak; Sinn, Marianne; Jurmeister, Philipp Sebastian; Biebl, Matthias; Weiß, Sascha; Rau, Beate; Bläker, Hendrik; Pratschke, Johann; Aigner, Felix
Mixed adenoneuroendocrine carcinomas of the gastrointestinal tract are until today poorly understood and thus very challenging for interdisciplinary therapy. We herewith report the first case series of patients with a primary mixed adenoneuroendocrine carcinoma of the rectum. Both cases were initially diagnosed as adenocarcinoma and only secondarily with mixed adenoneuroendocrine carcinoma and had a poor outcome due to a rapid tumor progression and resistance to chemotherapy. A 65-year-old female presented with local tumor recurrence and hepatopulmonary metastasis 1 year after primary surgery for adenocarcinoma of the rectum and consecutive radiochemotherapy regimen. Fluorouracil (5-FU) was followed by bevacizumab- and capecitabine-based chemotherapy but had to be discontinued due to side effects and progressive disease. Progressive local pain syndrome accompanied by recurrent bleeding episodes led to a local tumor-debulking operation. Afterward, mixed adenoneuroendocrine carcinoma as the underlying diagnosis in the final histopathological examination was detected. The patient died 3 months after the operation in the context of a fulminant tumor progress. A 63-year-old male patient underwent neoadjuvant radiochemotherapy and laparoscopic rectum resection. After 5 months, postoperative oxaliplatin/capecitabine-based adjuvant chemotherapy was switched to carboplatin/etopsid due to a progressive polyneuropathy and biopsy-proven pulmonary metastasis. The patient then had to be switched to local radiation of cerebral metastases and Topotecan due to cerebral bleeding episodes but died 18 months after the initial diagnosis. In conclusion of our case series, mixed adenoneuroendocrine carcinomas of the rectum should be considered as a rare but aggressive tumor entity. An early and detailed histopathological diagnosis is required in order to establish an individual interdisciplinary treatment concept.